Peningkatan Kompetensi Pedagogik Guru Melalui Pelaksanaan Supervisi Akademik - Lince Sirait (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2021)
The purpose of this study is to improve the pedagogical competence of teachers at SMAN 2 Siborongborong through academic supervision with classroom observation techniques. The research subjects were 9 non civil servant teachers. The data validity was done by triangulation. Data collection techniques using classroom observation instruments. The data analysis used was a comparative descriptive analysis technique. The results showed that in the initial conditions there were no teachers who met the indicators of success, there were only 3 teachers in sufficient criteria and 6 teachers in poor criteria with an average score of 1.99 in the poor criteria. After carrying out academic supervision activities with classroom observation techniques in the first cycle the results showed an increase in there were 4 teachers in good criteria and 5 teachers in sufficient criteria with an average score of 2.94 in sufficient criteria. In the second cycle all teachers have met the indicators of success with the explanation of 7 teachers in very good criteria and 2 teachers in good criteria with an average score of 3.60 in very good criteria